Lost but not forgotten--the economics of improving patient retention in AIDS treatment programs. - Gregory P Bisson; Jeffrey S A Stringer (PLoS Medicine, 2009)
Gregory Bisson and Jeffrey Stringer discuss the implications of a new study showing how loss to follow-up affects the effectiveness of a public sector HIV program in Côte d'Ivoire.